LEGAL MONITORING OF REGULATIVE LEGAL ACTS TO PROVIDE NATIONAL INTERESTS: THEORETICAL AND LEGAL ISSUES (Journal of actual problems of jurisprudence, 2023)
This article is dedicated to the investigation of a critical issue - legal monitoring of regulatory legal acts to safeguard national interests. The main objective of our research is to analyze theoretical and legal aspects related to this matter. This work represents a theoretical study that covers various aspects of monitoring regulatory acts and their role in securing the state's interests.Work holds both scientific and practical significance. The scientific importance of this work is evident in its contribution to a better understanding of the importance of legal monitoring of regulatory legal acts for safeguarding national interests. The practical value of this work lies in its potential use in the development of practical measures to ensure national interests through more effective legal monitoring of regulatory legal acts.This research enables a better understanding of the role of legal monitoring of regulatory legal acts in safeguarding national interests and contributes to the advancement of knowledge regarding legal monitoring of regulatory legal acts for the purpose of securing national interests and its significance for national security. Thus, our research can serve as a foundation for improving mechanisms for legal monitoring of regulatory legal acts to ensure national interests and can be beneficial for practitioners, legislators, and researchers.Key words: Legal monitoring; normative legal acts; national interests; theoretical and legal aspects; National security